Sharing dan Penyuluhan tentang Bahaya Narkoba di Lembaga Pemasyarakatan Khusus Anak (LPKA) - Fatiah, Mona S; Tambing, Yane; Irjayanti, Apriyana; Irab, Semuel Piter; Renti Br Tompul; Auriel Matui (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2024)
The widespread misuse of drugs, particularly Class I Narcotics, among teenagers in Papua Province, along with the high number of cases involving children detained as drivers and users in juvenile detention centers, has necessitated the implementation of one of the subjects, namely Prevention and Management of Narcotics, Psychotropic Substances, and Other Addictive Substances (NAPZA), at the Keerom District Juvenile Detention Center. Method: Community Engagement Activities (PkM) were carried out for one day on May 5, 2023, at the Keerom District Juvenile Detention Center, targeting an audience of 26 juvenile detainees. This PkM activity was executed using three methods: a question-and-answer session involving sharing activities with the juvenile detainees, Community Health Education (Penkesmas) in the form of a lecture on the dangers of drugs, and Data Collection, encompassing the gathering of data on the characteristics and knowledge of juvenile detainees concerning the hazards of drugs. Following the completion of the data collection phase, data analysis was conducted using STATA 24 software. Results: The majority of the detained children (50%) were 13 years old, with the highest level of education being the completion of High School (SMA) at 53.8%. There was a knowledge increase by 23.4% before and after the lecture. Conclusion: The implementation of the NAPZA subject through lectures resulted in a boost in the children's knowledge, and it was determined that the most widely consumed and circulated drug in Papua is Cannabis.